Art can provide a means for promoting biophilia as an aspect of zoonoses risk communication - Beaumont, Peyton (Frontiers in Conservation Science, 2024)
The COVID-19 pandemic served as a call to action for scientists to find new and creative ways to prevent future pandemics. Because value-based emotions underly human behavior, scientific facts alone have proven to be a poor motivator to change the behaviors that increase zoonotic spillover risk. Emotions can translate in psychological stances such as biophobia, the fear of or aversion to nature, and biophilia, the appreciation of nature. Educating the public about species that may pose a zoonotic risk can have the unintended effect of inducing biophobia into the public psyche. This can lead to increased zoonoses risk. In this Perspective, I make the case that strategically employing art can be an effective method to communicate zoonotic risk while promoting biophilia. Using art as a method of communication has been explored by various scientific fields but has not been sufficiently applied to infectious disease messaging.